(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2022)
A liquid/liquid extraction method was used to extract tartaric acid using the Amberlite LA-2 anion exchanger. The extraction efficiency of tartaric acid was determined under the influence of both the initial concentration of the acid and the initial concentration of the extractant Amberlite LA-2 at a contact time ranging from 15 to 60 minutes and at 25oC. The effect of pH and temperature effect on extraction efficiency was also studied under conditions of contact time of 30 minutes using an initial concentration of tartaric acid and Amberlite LA-2 to be 0.05 N and 0.022 N, respectively. The titration technique with sodium hydroxide was used to determine the concentration of tartaric acid in the aqueous layer before and after the extraction procedure. The experimental data were used to calculate distribution coefficients (KD), loading coefficients (Z), and extraction efficiency E%. The obtained results indicated that the extraction percentage E, %, increased with the increase of Amberlite LA-2 concentration, pH and temperature. An extraction efficiency of 99.5% was obtained, and a maximum loading of 1.318. The extraction process mechanism was also proposed.